Calculation and measurement of doses in the surface layers of a phantom when using Tomotherapy - Kowalik, Anna (Rep Pract Oncol Radiother, 2019)
BACKGROUND: The calculation and measurement on the surface of the skin presents a significant dosimetric problem because of numerous factors which have an influence on the dose distribution in this region. AIM: The overall aim of this study was to check the agreement between doses measured with thermoluminescent detectors (TLD) during tomotherapy photon beam irradiation of the skin area of a solid water cylindrical phantom with doses calculated with Hi-Art treatment planning system (TPS). MATERIAL AND METHOD: The measurements of the dose were made with the use of a solid water cylindrical phantom - Cheese Phantom. Two bolus phantoms were used: 5 mm and 10 mm Six different planning treatments were generated. The doses were measured using TL detectors. RESULTS: In the case of a tumor located near the surface of the skin, the mean dose for 0.5 cm bolus was - 1.94 Gy, and for 1 cm bolus - 2.03 Gy. For the tumor located inside the phantom and organ at risk on the same side that TL detectors, for a 0.5 cm bolus, mean dose was 0.658 Gy, and for a 1 cm bolus, 0.62 Gy. CONCLUSION: The analysis of results showed that the relative percentage difference between measured and planned dose in the field of irradiation was less than 10%, while the largest differences were on the board of the field of radiation and outside of the field of irradiation, where the dose was 0.08 Gy to 1 Gy.